Does Financial Development Enhance Foreign Trade in Selected Transitional Economies? - Kunofiwa Tsaurai; Patience Hlupo (Comparative Economic Research. Central and Eastern Europe, 2020)
The study investigates the influence of financial development on foreign trade in transi- tional economies using panel data (1994-2014). Although empirical studies on the im- pact of financial development on foreign trade are available, none of them that the au- thors are aware of attempted to explore the subject matter in the context oftransitional economies. None attempted to investigate if human capital development is a channel through which financial development influences foreign trade or international trade. Under fixed effects, financial development was found to have a non-significant posi- tive influence on foreign trade, while the random effects approach shows a significant positive relationship running from financial development towards foreign trade. The findings resonate with the majority of the literature on the subject. However, pooled ordinary least squares (OLS) shows that financial development had a significant nega- tive influence on foreign trade. Under both fixed and random effects, human capital development was found to be a channel through which financial development had a significant positive effect on foreign trade. The results are in line with Patrick's (1966) argument that foreign trade is quickened by high levels of human capital and financial development. The implication of the study is that transitional authorities should develop and implement human capital development enhancement policies in order to enable financial de- velopment to have a significant positive effect on foreign trade. In contrast to the available literature, human capital development was found to have had a significant negative impact on foreign trade under the OLS approach. Future studies on the sub- ject matter should address the endogeneity concerns and the dynamic characteristics of the foreign trade data.
Keywords: G15; J24; P45; P2; 330; Financial Development; Foreign trade; Transitional Economies; Panel Data; Finanzsystem; Humankapital; Außenhandel; Wirtschaftswachstum; Transformationsstaaten; Schwellenländer